THE EFFECTIVENESS OF QUALITY CONTROL ANALYSIS WITH SIX SIGMA METHODOLOGY IN EFFORT TO MINIMIZE NUMBER OF DEFECTS IN MUSICAL INSTRUMENT MANUFACTURING INDUSTRY CASE STUDY OF PT GENTA TRIKARYA - Irwansyah, Anjas; Handayati, Yuanita (Journal of Business and Management, 2021)
Quality is one of the key successes of company to meet customer demand. Quality management is the internal process and one of its parts is Quality Control as main point in this research. The object research is PT Genta Trikarya as one of the many guitar assembly industries in Indonesia. Currently the implementation of QC at each stage of the business process has a lack of optimality or poor performance especially for three QCs that produced the most defects would be more concerned, which led to a significant increase in number of defects from 2019 to 2020. To overcome the problem, the suitable methodology is Six Sigma Methodology as the problem solving and continuous improvement process. Therefore, this research aims to minimize number of defects. The data collected by using qualitative data approach through semi-structured interview and observation as primary data, and report as secondary data, for the informants are Quality Manager and Polish QC Staff. The data were analysed by using DMAIC approach which consists of Define, Measure, Analyse, Improve, and Control. For QCs’ poor performance need to be trained to create better performance for next processes as one of the most important proposed solutions. This research can be said useful especially for PT Genta Trikarya as the object research.Keywords: Quality Management, Quality Control, Six Sigma Methodology, DMAIC, Defects